Mathematical modelling of droplet atomization using the population balance equation - S. Aly, Hossam (Institute of Electrical and Electronics Engineers, 2009)
This study investigates numerically the atomization process occurring in a plain jet airblast atomizer. The population balance equation is solved for the dispersed phase coupled with a CFD Eulerian multi-fluid model. The Sauter mean diameter values obtained numerically compare favorably with previous experimental data only at certain flow conditions. Finally, this study proposes some enhancements on using the numerical model which were revealed from the model formulation and the results obtained.